Structure Analysis Of Fe3O4-Graphene Oxide Nanocomposite From Corn Cob Waste - Ismira, Ismira; Hidayat, Rahmat; Ratnawulan, Ratnawulan; Jonuarti, Riri (Journal of Experimental and Applied Physics, 2024)
This research is a study of the structure of nanocomposites whose composition is varied between Fe3O4 and Graphene Oxide. The purpose of this study is to determine the structure of Fe3O4-Graphene Oxide nanocomposites from corn cob waste. This type of research is experimental research, which begins with sample preparation from corn cob waste, carbon activation, graphene oxide synthesis, sonication and neutralization of graphene oxide, and synthesis of Fe3O4-Graphene Oxide nanocomposites using the ball milling method by varying the composition. Crystal size and structure were characterized by XRD, functional groups were characterized by FTIR, surface morphology, particle size and porosity were characterized by SEM. The results of the research on the structure of Fe3O4-Graphene Oxide nanocomposites from corn cob waste, obtained XRD results show that the crystal structure is Hexagonal, Cubic, and Orthorhombic with the average crystal size of the best Fe3O4-Graphene Oxide composition variation at 30%: 70% composition, because the particle size produced is quite small from other composition variations, namely 39.19 nm. FTIR results show that all compositional variation comparisons have C-H, O-H, C≡C, C=O, C=C, C-O, and Fe-O bond functional groups. SEM results show the morphology of Fe3O4 is spherical, while the morphology of graphene oxide is in the form of chunks. The particle size value gets smaller as the Fe3O4 composition increases, because the more Fe3O4 composition causes the surface of the graphene oxide particles covered to get bigger. In addition, particle size can also affect the porosity of nanocomposites, the smaller particle size can increase porosity because more particles can occupy space.